Multiple recombination events between field and vaccine strains resulted in the emergence of a novel infectious bronchitis virus with decreased pathogenicity and altered replication capacity - Mengting Ren (Poultry Science, 2020)
In this study, we isolated and identified 2 infectious bronchitis virus (IBV) strains from layer chickens soon after vaccination with the Massachusetts–Connecticut bivalent vaccine (Conn) and H120 and 4/91 booster vaccines in China in 2011. The results of cross-virus-neutralization tests and phylogenetic analysis of the S1 subunit of spike gene of these vaccine strains and other reference strains showed that strain LJL/110302 was of GI-19 lineage, whereas LLN/111169 was of the GI-1 lineage of the Conn serotype. Further comparative genomic analysis revealed that LLN/111169, an IBV strain with novel traits, originated from multiple recombination events (at least 3 recombination sites) between GI-19 and the Conn and 4/91 vaccine strains. LLN/111169 was pathogenic to specific pathogen-free (SPF) chickens. This is of prime importance because while IBV prevention measures worldwide are mainly dependent on modified live vaccine strains, our results showed that recombination between field and vaccine strains has produced a novel pathogenic IBV strain. In addition, LLN/111169 showed relatively broad tissue tropism (trachea, lungs, kidneys, and cecal tonsils) in infected SPF chickens. These results emphasize the importance of IBV surveillance in chicken flocks.